Islamic Education Institutions with Sufism Characteristics in Classic Times (Ribath, Zawiyah, and Khanqah) - Rafika Nisa; Muhamadaree Waeno (IJIE International Journal of Islamic Education, 2022)
The heyday of Islam was when Islamic education developed rapidly, marked by the development of Islamic educational institutions and traditional schools and universities in various Islamic cultural centers. Educational institutions greatly influence and shape the pattern of life and culture of Muslims. Islamic educational institutions with a Sufism design have become part of the ongoing process of the history of educational thought in the classical period of Islam. Therefore, this discussion will focus on tracing the development of ribath, zawiyah, and khanqah institutions, starting from the curriculum, methods, and their contribution to Islamic intellectual progress in general. The purpose of this study is to present a tracing of the development of Islamic educational institutions with a Sufism nuance because the institutions have contributed to the intellectual progress of Islam and are reflected in the history of human socio-cultural development on earth. This research is a literature study using literature from various sources. The survey results show that Sufism institutions (Ribath, Zawiyah, and Khanqah) contribute to the growth of Islamic educational institutions in restoring spiritual purity and inner peace in Sufi teachings. Its teachings include curriculum, and methods that promote a spiritual closeness to Allah Swt, formalize Sufism as a separate scientific subject, increase social power through the organization, revive Sufi traditions, and serve as a distinct way of understanding and practicing Islam.